System information accounting in business performance: A systematic literature review - Maulina, Baiq Farida; Nazaruddin, Ietje (Journal of Accounting and Investment, 2025)
Research Aims: This study evaluates journals discussing the impact of Accounting Information Systems (AIS) on Business Performance to derive useful lessons for addressing future challenges.Design/Methodology/Approach: Using a review framework adapted from Hoque (2014), this study analyzes 58 journals selected through a keyword search ("Accounting," "Information," "System," and "Business Performance"). Themes were identified, and findings are discussed based on the origin of studies and their implications.Research Findings: Four key themes emerged: (1) Innovation Performance – highlighting the role of strategies in enhancing productivity and growth; (2) Innovation Capability – focusing on integrating knowledge and resources for better innovation; (3) Government Regulation – examining financial support and training for business growth; and (4) Competitive Advantage – emphasizing strategic management's role in achieving superior business outcomes.Theoretical Contribution/Originality: The study identifies gaps in research related to emerging technologies like blockchain, AI, and cloud computing while also highlighting trends such as sustainability, security, and AIS’s evolving role in strategic decision-making.Practical Implications: Business leaders can use AIS for better decision-making, governments can design supportive policies, and academics can explore innovative frameworks integrating technologies like AI and blockchain to improve business performance and competitiveness.Research Limitations/Future Directions: Future studies should investigate the integration of blockchain for transparency, AI for automation and fraud detection, cloud-based AIS for security and collaboration, and big data for forecasting and ESG reporting. Additionally, the impact of government regulations on AIS adoption requires further analysis.